2020
DOI: 10.1186/s13104-020-05001-9
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of circulating miR-320a and target gene prediction in patients with diabetic retinopathy

Abstract: Objective: To evaluate the expression of a set of miRNAs to identify differentially expressed miRNAs that might be considered reliable biomarkers on Diabetic Retinopathy (DR) blood samples. were analyzed in 60 healthy controls, 48 Diabetes Melitus (DM) without DR patients and 62 DR patients by qRT-PCR. MiR-320a was shown to be downregulated in the plasma of DR patients compared with DM patients without DR and healthy subjects. Target genes were predicted using miRWalk3.0, miR targeting data and target gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A number of studies have indicated the role of miRNAs in tumors ( 29 , 30 ). miR-320a, which is an extensively studied miRNA, has been reported to serve a critical role in diabetic retinopathy ( 31 ) and atherosclerosis ( 32 ). Moreover, miR-320a has been investigated in several types of cancer, such as lung cancer ( 33 ), papillary thyroid cancer ( 34 ), osteosarcoma ( 35 ) and hepatocellular carcinoma ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated the role of miRNAs in tumors ( 29 , 30 ). miR-320a, which is an extensively studied miRNA, has been reported to serve a critical role in diabetic retinopathy ( 31 ) and atherosclerosis ( 32 ). Moreover, miR-320a has been investigated in several types of cancer, such as lung cancer ( 33 ), papillary thyroid cancer ( 34 ), osteosarcoma ( 35 ) and hepatocellular carcinoma ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addtion, using an RNA-Seq approach, it was evidenced that miR-4448, miR-338-3p, miR-190a-5p, miR-485-5p, and miR-9-5p appeared differentially expressed in serum from retinopathic diabetic patients when compared to controls (49). However, while validation of miR-21 and miR-126 in DR was confirmed in other similar studies (39,40,44,45), miR-320a, which was previously found to be upregulated in DR (23), was later reported to be significantly downregulated in another work (51), indicating, therefore, that discrepancies exist in this context. Several explanations can be provided for the lack of consensus in the literature in this regard.…”
Section: Discussionmentioning
confidence: 72%
“…In recent years, several works have investigated the association of miRNAs with DR (23)(24)(25)(26)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In circulating miRNA profiling studies, miR-27b, miR-320a, and miR-126 were validated in patients with type 1 diabetes and DR (23,42).…”
Section: Discussionmentioning
confidence: 99%
“…DR is one of the most extensively studied diabetic complications, since it is a major cause of blindness and vision impairment among adults. Plasma levels of miR-320a are lower in patients with DR compared to patients with DM and no retinopathy and to healthy controls [ 89 ]. MiR-320 is also involved in the regulation of insulin growth factor-1 (IGF-1) expression, which takes part in the development of insulin resistance in adipose tissue and endothelial cells [ 89 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Plasma levels of miR-320a are lower in patients with DR compared to patients with DM and no retinopathy and to healthy controls [ 89 ]. MiR-320 is also involved in the regulation of insulin growth factor-1 (IGF-1) expression, which takes part in the development of insulin resistance in adipose tissue and endothelial cells [ 89 ]. It is noteworthy that patients with DR presented with higher risk of AD compared to healthy controls, indicating the association between dysregulated miRNAs, DM, DR and AD [ 90 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%